The Past, Present, and Future of General Simulation Languages - Krasnow, Howard S.; Merikallio, Reino A. (Management Science, 1964)
The widespread use of simulation in the design and analysis of complex systems has received a great impetus in the past few years with the advent of various general simulation languages. Simulation models of a wide variety of physical situations can now be developed with these languages. This paper summarizes and compares various characteristics of five major general simulation languages. The historical background from which these languages developed is discussed first. Predictions are also made on the future development of general simulation languages.